Research management in times of increasing complexity: Towards the construction of new cartographies - Barbera Alvarado, Nataliya; Chirinos Arque, Yamarú del Valle; Godinez, Roberto; Perez Peralta, Claudia Milena (Revista de Ciencias Sociales, 2023)
Aware that reality is characterized by being multiform and with arbitrary variables, this article aims to reflect on the epistemic foundations required in the management of research in times of increasing complexity as mechanisms for the construction of new cartographies. It was addressed under the documentary research method, using the content analysis and summary sheet as recording techniques of the information extracted from the bibliographic sources consulted. The results indicate that the classical vision of science has imposed a rationality based on empiricism and mathematical rationalism, conducting the investigative work through fixed territories, approaching reality with a single method. However, currently rigorous scientific practice is not limited to standards or a priori models. An ontological understanding is required to locate and select the appropriate method that provides a relevant solution to the research problem. Finally, it is concluded that it is time to dethrone the traditional authority to think and act from the complementary articulation of scientific logics and/or rationalities, which lead to an epistemological turn that invites to combine pure reason with social knowledge, monological with multi-methods, analytical thinking with polyvocal thinking.